2022
DOI: 10.1002/lno.12214
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of dissolved organic matter by two Indo‐Pacific sponges

Abstract: Dissolved organic matter (DOM) is the largest organic carbon reservoir in the ocean and an integral component of biogeochemical cycles. The role of free-living microbes in DOM transformation has been studied thoroughly, whereas little attention has been directed towards the influence of benthic organisms. Sponges are efficient filter feeders and common inhabitants of many benthic communities circumglobally. Here, we investigated how two tropical coral reef sponges shape marine DOM. We compared bacterial abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
4
7
0
Order By: Relevance
“…This corresponds to 10 to 18% of the recycled N in the oligotrophic west Australian continental shelf (Keesing et al, 2013). Sponges are also a major transformer of dissolved organic matter (DOM) (Hildebrand et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to 10 to 18% of the recycled N in the oligotrophic west Australian continental shelf (Keesing et al, 2013). Sponges are also a major transformer of dissolved organic matter (DOM) (Hildebrand et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This corresponds to 10 to 18% of the recycled N in the oligotrophic west Australian continental shelf (Keesing et al, 2013). Sponges are also a major transformer of dissolved organic matter (DOM) (Hildebrand et al, 2022). Sponges are holobionts (Webster and Taylor, 2012) consisting of the sponge itself and a microbial community that can contribute up to 38% to the overall sponge holobiont volume (Vacelet, 1975).…”
mentioning
confidence: 99%
“…The composition and structure of DON differ among variable sources (Y. Li et al., 2019; Petrone et al., 2008). As a major fraction of dissolved organic matter (DOM), DON is in line with dissolved organic carbon (DOC) in coastal waters (Hildebrand et al., 2022; Lee et al., 2020). This synergistic change enables the characterization of DON using similar techniques, such as ultraviolet‐visible (UV‐vis) adsorption spectroscopy and the emission‐excitation matrix combined with parallel factor analysis (EEM‐PARAFAC), to explore its composition and distinguish its sources (Osburn et al., 2016; L. Wang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Among sponges, the massive Rhabdastrella globostellata (Carter, 1883) is the most abundant species at Bouraké, reaching up to 40 % cover (Maggioni et al, 2021). This Indo-Pacific high microbial abundance (HMA) species (Moitinho-Silva et al, 2017a) has been demonstrated to efficiently filter bacteria cells and remove DOM from surrounding seawater (Hildebrand et al, 2022), fundamentally altering its composition.…”
Section: Introductionmentioning
confidence: 99%